Prevalence and clinical characteristics of chronic spontaneous urticaria in pediatric patients - Balp, Maria‐Magdalena; Weller, Karsten; Carboni, Veruska; Chirilov, Alexandra; Papavassilis, Charis; Severin, Thomas; Tian, Haijun; Zuberbier, Torsten; Maurer, Marcus (Pediatric allergy and immunology, 2018)
Background Data on the prevalence and disease management of chronic urticaria (CU) and chronic spontaneous urticaria (CSU) in the pediatric population are scarce. This study assessed the prevalence of CU and CSU, and disease management among pediatric patients (0‐17 years). Methods A physician‐based online survey was conducted in 5 European countries (United Kingdom, Germany, Italy, France, and Spain) assessing the annual diagnosed prevalence, disease characteristics, and treatment patterns in the target population. Results are based on physician responses and analyzed using descriptive statistics. Prevalence estimates were calculated based on the number of CU/CSU pediatric patients diagnosed, seen, and treated by the respondents and extrapolated to the total pediatric population from each country. Results Across 5 European countries, the one‐year diagnosed prevalence of CU and CSU in pediatric patients was 1.38% (95% CI, 0.94‐1.86) and 0.75% (95% CI, 0.44‐1.08), respectively. Angioedema was reported in 6%‐14% of patients. A large proportion of CSU pediatric patients (40%‐60%) were treated with H1‐antihistamines at approved dose and 16%‐51% received H1‐antihistamines at higher doses. Approximately 1/3 of pediatric CSU patients remained uncontrolled with H1‐antihistamines at approved/higher doses. Other prescribed treatments were oral corticosteroids (10%‐28%) and topical creams (15%‐26%). Conclusions This study revealed a prevalence of CSU among pediatric population comparable to adults and also suggested an unmet need for approved treatments for inadequately controlled pediatric CSU patients. It is truly of concern that harmful (oral steroids) or insufficient (topical creams) treatments were frequently used despite better and guideline‐recommended alternatives.